Optimization and Evaluation of Noni Leaf Skin Softening Lotion Preparation (Morinda Citrifolia L.) - barus, bunga rimta; Ilsanna Surbakti, Christica; Salman, Salman (Universitas Negeri Medan, 2025)
The premature aging process is usually characterized by visible wrinkles or wrinkles on the face, dry and rough skin, age spots and decreased skin elasticity. Noni leaves (Morinda citrifolia L.) are one type of herbal plant that can potentially act as an antioxidant. The purpose of this study was to see Optimizing the Formulation of Lotion Preparations and Evaluating the Physical Properties of Lotion Preparations. Noni leaves were macerated with 96% ethanol solvent and then rotary with an evaporator. Hand and body lotion preparations were made by adding ethanol extract of noni leaves with several concentrations of 2.5% (F1), 5% (F2), and 7.5% (F3) to the base of hand and body lotion. As a blank (F0) the base of hand and body lotion without ethanol extract of noni leaves. Testing on the preparation was an evaluation of stability for 4 weeks at room temperature (odor, color, pH, emulsion type, homogeneity), irritation test and anti- aging skin activity test using a skin analyzer on hand skin. The parameters measured included water content, pore size, number of blemishes and number of wrinkles. Treatment was carried out using hand and body lotion every day for 4 weeks. Ethanol extract concentrations of 2.5%, 5% and 7.5% were homogeneous preparations with an oil-in-water emulsion type, pH 6.3-6.8, stable in storage for 4 weeks, and did not irritate the skin. Anti- aging skin hand and body lotion preparations containing ethanol extract of noni leaves can increase water content, reduce pore size, reduce the number of blemishes, reduce the number of wrinkles on the skin of the back of the hand and are stable in storage for 4 weeks. Hand and body lotion preparations with ethanol extract at a concentration of 7.5% had better skin antiaging activity compared to concentrations of 2.5%, 5% and blank.